2013
DOI: 10.1021/bi301412n
|View full text |Cite
|
Sign up to set email alerts
|

Photocycle and Vectorial Proton Transfer in a Rhodopsin from the Eukaryote Oxyrrhis marina

Abstract: Retinylidene photoreceptors are ubiquitously present in marine protists as first documented by the identification of green proteorhodopsin (GPR). We present a detailed investigation of a rhodopsin from the protist Oxyrrhis marina (OR1) with respect to its spectroscopic properties and to its vectorial proton transport. Despite its homology to GPR, OR1's features differ markedly in its pH dependence. Protonation of the proton acceptor starts at pH below 4 and is sensitive to the ionic conditions. The mutation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
4
16
0
Order By: Relevance
“…An absorbance maximum at 519 nm was registered for the recombinant wild-type protein. The shoulders toward shorter wavelengths in the spectra of B2, B3, and B4 in the current study were previously also reported by Jahnke et al [22]. The 280/519 nm ratios calculated for B2, B3, and B4 (if present) are rather high and most likely due to the presence of TX-100, which shows absorbance at 280 nm.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…An absorbance maximum at 519 nm was registered for the recombinant wild-type protein. The shoulders toward shorter wavelengths in the spectra of B2, B3, and B4 in the current study were previously also reported by Jahnke et al [22]. The 280/519 nm ratios calculated for B2, B3, and B4 (if present) are rather high and most likely due to the presence of TX-100, which shows absorbance at 280 nm.…”
Section: Discussionsupporting
confidence: 90%
“…Oesterhelt and Stoeckenius [4] calculated a value of 2 for the 280/560 nm ratio of the bacteriorhodopsin of H. salinarum . Similar values of approximately 2 have been reported for the recombinant wild‐type protein and point‐mutated derivatives of ABV22426 by Janke et al [22]. These proteins, however, were heterologously expressed and purified by His‐tagged metal affinity chromatography.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…More than a quarter of century later, a chain of discoveries established widespread presence of protonpumping rhodopsins in marine and freshwater eubacteria, and these proteins became known as proteorhodopsins (PR), xanthorhodopsins (XR) and actinorhodopsins [17][18][19][20]. In parallel, it was realized that various lower eukaryotes, including multiple fungi and some algae, possess retinalbinding light-driven proton pumps as well [21][22][23][24]. Biophysical studies of proton transport in these newly discovered rhodopsins provided information on the essential (conserved) and optional (variable) elements in its molecular mechanism [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial rhodopsin was fi rst known from halorhodopsin in Halobacterium . A variant of this rhodopsin, known as proteorhodopsin, is found not only among α- (Stingl et al 2007 ), β-, and γ-proteobacteria, such as the classical organoheterotroph Vibrio campbellii (Wang et al 2012 ), but also among Bacteriodetes (Gómez-Consarnau et al 2007, González et al 2008Riedel et al 2010 ), Archaea , and eukaryotes (Janke et al 2013 ). Although proteorhodopsin is related to halorhodopsin and other "microbial" (type I) rhodopsins, it forms a very distinct clade (McCarren and DeLong 2007 ;Fig.…”
Section: Photoheterotrophy In the Oceanmentioning
confidence: 99%